Digital innovation strategy for creative industries: responding to competition challenges in the digital age - Aryanti, Asti Nur; Suryana, Suryana; Hendrayati, Heny; Rahmi, Palupi Permata; Wijaya, Fanji; Herlina, Listri (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2023)
The creative industries should be able to keep up with competitors' strategies to survive in the contemporary business environment. The depth of the digital touch in every company operation encourages business people to adapt it while developing new products. The purpose of this study was to present an overview of the digital-based innovation strategies employed by the leading creative industries in Bandung. Using a descriptive analysis strategy, the research method employed was qualitative. Techniques for data collection included literature reviews, field investigations, questionnaires, and in-depth interviews. The study's findings demonstrated that strategies for digital-based innovation were not conducted to their full potential. In this particular industry, there was insufficient growth of digitally based products and services, limited responsiveness to digital solutions provided by competitors, a lack of differentiation from competitors, relatively few platforms for digitally based products that were different from competitors, and poor product development. There were no newly developed digital products on the market. In addition, only the process innovation strategy received a positive response regarding the dimensions of a digital-based innovation strategy, even though most were still far from the digitalization process. However, digital implementation was absent from the organization's marketing and product innovation strategies, making them appear inefficient